2006
DOI: 10.1016/j.neubiorev.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The correlative triad among aging, dopamine, and cognition: Current status and future prospects

Abstract: The brain neuronal systems defined by the neurotransmitter dopamine (DA) have since long a recognized role in the regulation of motor functions. More recently, converging evidence from patient studies, animal research, pharmacological intervention, and molecular genetics indicates that DA is critically implicated also in higher-order cognitive functioning. Many cognitive functions and multiple markers of striatal and extrastriatal DA systems decline across adulthood and aging. Research examining the correlativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
569
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 705 publications
(599 citation statements)
references
References 143 publications
(191 reference statements)
21
569
0
9
Order By: Relevance
“…In the present study, all the participants in the group of older adults were at least 70 years of age. Therefore, first signs of senescent reductions in neuronal mass (Sowell et al, 2003), and in neurotransmitter availability are likely (Backman and Farde, 2005;Backman et al, 2006;Li et al, 2001), even in early visual processing areas, which are known to be well preserved in aging (Raz et al, 2005). Furthermore, It has been shown that gamma-band activity is modulated by genetic polymorphisms (Demiralp et al, 2007) and psychiatric disorders (Gallinat et al, 2004;Herrmann and Demiralp, 2005) affecting dopaminergic neu-romodulation.…”
Section: Evoked Gamma-band Responses Of Early Visual Processing In Olmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, all the participants in the group of older adults were at least 70 years of age. Therefore, first signs of senescent reductions in neuronal mass (Sowell et al, 2003), and in neurotransmitter availability are likely (Backman and Farde, 2005;Backman et al, 2006;Li et al, 2001), even in early visual processing areas, which are known to be well preserved in aging (Raz et al, 2005). Furthermore, It has been shown that gamma-band activity is modulated by genetic polymorphisms (Demiralp et al, 2007) and psychiatric disorders (Gallinat et al, 2004;Herrmann and Demiralp, 2005) affecting dopaminergic neu-romodulation.…”
Section: Evoked Gamma-band Responses Of Early Visual Processing In Olmentioning
confidence: 99%
“…Results from post-mortem studies of the brain, magnetic resonance imaging (MRI), functional MRI, as well as electrophysiological studies indicate that human brain development can be characterized as non-linear and heterochronous, with different parts of the brain follow different developmental time courses (Gogtay et al, 2004;Sowell et al, 2003;Thatcher, 1992;Thatcher et al, 1986). Besides lifespan changes in brain structure and connectivity, the availability and expression of neurotransmitters (especially dopamine) also changes and affects cognitive functioning (for reviews, see Backman et al, 2006;Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recent studies have sought to investigate the relationship between structural age-related degeneration of gray and white matter in these regions and learning and recall (Brickman et al, 2007;Buckner, 2004;Craik, 2006;Mungas et al, 2005;Schiltz et al, 2006). However, it has also been pointed out that AAMI is not only a result of degeneration of prefrontal and MTL regions but also a result of age-related dysfunction in cholinergic (Mesulam, 2004b) and dopaminergic (DA) (Backman et al, 2006) neuromodulation. The focus of the present study is on these neuromodulatory influences.…”
Section: Introductionmentioning
confidence: 99%
“…Also, cholinergic neuromodulation is implicated in the ability to maintain stimulus information online in working memory (Hasselmo and Stern, 2006). Both dopaminergic and cholinergic neuromodulation undergo age-related degeneration (for reviews, see Backman et al (2006)). Human autopsy data indicate a 3% age-related decrease in dopamine D1 (Cortes et al, 1989;Rinne et al, 1990;Seeman et al, 1987) and D2 receptors (Seeman et al, 1987) per decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation